2021
DOI: 10.3390/sym13040555
|View full text |Cite
|
Sign up to set email alerts
|

Walking on a Vertically Oscillating Platform with Simulated Gait Asymmetry

Abstract: Asymmetric gait is associated with pain, injury, and reduced stability in patient populations. Data from side by side walking suggest that unintentional synchronization with an external cue may reduce gait asymmetry. Two types of asymmetric gait were examined here: (1) mass imbalance between limbs to simulate single limb amputation and (2) restriction of plantarflexion during toe-off to simulate reduced propulsion from neurological impairment. Twenty-five healthy participants walked normally and with simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Previous research has suggested that unilateral limb dominance caused by differences in the dominant functions upon the two hemispheres of the brain is one of the causes of bilateral asymmetry in normal gait [ 11 ], gait asymmetry associated with natural functional differences between the two limbs can also lead to bilateral musculoskeletal mass and strength imbalances [ 13 ]. Simultaneously, greater lower limb asymmetry necessitates more energy to walk, and prolonged asymmetrical walking can place additional strain on the lower limb joints and accelerate degenerative joint changes [ 14 ]. Therefore, gait asymmetry is an important factor affecting walking efficiency and safety, reduced lower limb asymmetry allows the limb to make faster transitions in response to disturbances, lowering the risk of falling.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that unilateral limb dominance caused by differences in the dominant functions upon the two hemispheres of the brain is one of the causes of bilateral asymmetry in normal gait [ 11 ], gait asymmetry associated with natural functional differences between the two limbs can also lead to bilateral musculoskeletal mass and strength imbalances [ 13 ]. Simultaneously, greater lower limb asymmetry necessitates more energy to walk, and prolonged asymmetrical walking can place additional strain on the lower limb joints and accelerate degenerative joint changes [ 14 ]. Therefore, gait asymmetry is an important factor affecting walking efficiency and safety, reduced lower limb asymmetry allows the limb to make faster transitions in response to disturbances, lowering the risk of falling.…”
Section: Introductionmentioning
confidence: 99%